Development of a bath challenge for the marine shrimp Penaeus vannamei Boone, 1931 - A. Roque (2018)
Despite the major financial losses caused by vibriosis in shrimp culture, no reliable laboratory model has yet been developed for this disease. A reproducible experimental model is therefore urgently required for further study. In this study, a bath challenge technique was developed for juveniles of the marine shrimp Penaeus vannamei. Four different treatments were applied to the shrimp: (1) shrimps were wounded on the third abdominal segment and were immediately exposed to a bath of Vibrio parahaemolyticus afterwards; (2) shrimps were only wounded; (3) shrimps were only exposed to V. parahaemolyticus; and (4) control, shrimps were neither wounded nor challenged. The experiment was repeated four times to verify the reproducibility of the technique. All the mortalities occurred within four days and the cumulative mortalities were significantly different between treatments: varying from 37 to 52% for the first treatment, 12 to 22% for the second, 0 to 13% for the third, and 0 to 3% for the control.